Production and Investigation of Biodiesel Fuels from Spent Coffee Grounds - Mustafa, Zilya; Yordanov, Dobromir; Milina, Rumyana (Journal of Technology Innovations in Renewable Energy, 2017)
The oil fractions, extracted under different conditions from spent coffee grounds, were used to produce biodiesel fuels and investigate their FAME profiles. For producing of fuels, esterification and transesterification of oils with homogeneous catalysts were applied. Investigation of the esters composition (FAME) in biodiesel is carried out by modified gas chromatographic method EN 14103. The content of each individual ester was calculated using the method of internal standard. The results of total and individual FAME content in all studied objects are shown. The results show the feedstocks and extraction conditions (catalysts, temperatures) for obtaining the biodiesel with high yield and balanced composition.